مفهوم الأدب بين الأدباء العرب والأدباء الملايويين بماليزيا دراسة تقابلية = The concept of Islamic literature between Arab and Malay writers: a comparative study - Yaacob, Adli (IIUM, 2014)
This article focuses on the idea of Islamic Literature which began in the Arab world through the writings of Muhammad Qutb, Syed Qutb, Naj ib al - Kilani, Emaduddin Khalil and a few others who came after them, influenced by their ideas. Later, concepts or theories of Islamic Literature began to take shape among the writers. In Malaysia, the concept was presented by Syed Muhammad Naquib Al - ‘Atta s who said that a writer must have a balanced views in the soul, body and mind. After him, there was Affandi Hassan who came up with something unconventional on the theory of Islamic literature. A number of other writers also tried to conceptualize the Isl amic literature such as Shafie Abu Bakar, Kamala, ‘Ali Ahmad, Uthman el - Muhammady and Muhammad Kamal Hasan who tried to come up with the realistic view on Islamic literature based on what was suggested by another writer, Shahnon Ahmad. Another scholar, Kas ssim Ahmad tried to dwell on the issue of methodology in Islamic literature. Ismail Ibrahim, another scholar, suggested that Islamic literature must stand on the principle of the unity of God (tawheed). This paper intends to study the concept of Islamic Li terature and its development among the Arab and Malay writers. A comparative study on the similarities and differences of these concepts will also be a focus. Keywords: Islamic Literature, concept, differences, similarities